THE ROLE OF AROMATASE IN THE DEVELOPMENT OF ENDOMETRIOSIS - L. V. Adamyan; M. M. Sonova; O. N. Loginova; K. N. Arslanyan (IRBIS LLC, 2017)
The purpose of work - improving the efficiency of treating endometriosis by clarifying some aspects of the pathogenesis of endometriosis.Objectives of the study - determining the expression of aromatase in atopicescom and ectopic endometrium, to identify the relationship of polymorphisms in the aromatase gene and gems of detoksikatsii to optimize the ingenious treatment of patients with endometriosis.Materials and methods. Definition of polymorphic gene variants of CYP19 was assessed by PCR with specific oligoprimers with subsequent restriction analysis.Results: the Expression of aromatase in the studied forms of endometriosis is positively correlated with the stage of disease. The "zero" variant of the gene GSTМ associated with pelvic pain of varying intensity, as well as recurrent forms of the disease (χ2 =of 8.78; p<0.05), which is important in the prediction of the clinical course of the disease. By gene GSTT1 any difference in the groups, as well as links with clinical manifestations of endometriosis was obtained.Conclusion. Detection of positive expression of aromatase in the ectopic foci, and also in the endometrium atopicescom when adenomiose (58%) and external endometriosis (80%), its relationship with stage distribution of the disease and the severity of pain allows us to consider this enzyme as a promising for the diagnosis and development of new approaches to the treatment of endometriosis with aromatase inhibitors. The study of associated gene polymorphisms of the aromatase CYP19 and detoxification GSTM can be recommended as a prognostic test for assessing the risk of development and prognosis the clinical course of endometriosis.